Health Based Parenting Education for Child Physical and Mental Wellbeing: Pendidikan Orang Tua Berbasis Kesehatan untuk Kesejahteraan Fisik dan Mental Anak - Dzulqarnain Andira (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Parenting practices play a central role in supporting children’s physical and mental wellbeing within family and community settings. Specific Background In rural areas, including Desa Kalipecabean, parenting remains largely conventional and has not fully adapted to contemporary challenges related to child mental health and family dynamics. Knowledge Gap Limited community-based initiatives have systematically addressed parenting education grounded in child health perspectives for rural populations. Aims This community service activity aimed to increase parental understanding of healthy, supportive, and evidence-based parenting related to children’s physical and mental health. Results The activity, delivered through interactive lectures and discussions involving fathers and mothers, demonstrated increased participant understanding of the relationship between parenting patterns and child physical and mental health, as well as heightened awareness of the shared role of both parents in childrearing. Novelty This program integrates health-based parenting education within a rural community service framework that explicitly addresses both physical and mental dimensions of child wellbeing. Implications The findings indicate that health-oriented parenting education can serve as a promotive and preventive approach in rural communities to support healthier family environments and optimal child development. Highlights: Parental understanding of links between caregiving practices and child wellbeing increased after the activity Shared involvement of fathers and mothers in childcare was recognized as essential Interactive community-based education addressed contemporary parenting challenges in rural settings Keywords: Parenting, Child Health, Mental Health, Community Service, Village.